2017
DOI: 10.1186/s12864-017-3976-z
|View full text |Cite
|
Sign up to set email alerts
|

High resolution measurement of DUF1220 domain copy number from whole genome sequence data

Abstract: BackgroundDUF1220 protein domains found primarily in Neuroblastoma BreakPoint Family (NBPF) genes show the greatest human lineage-specific increase in copy number of any coding region in the genome. There are 302 haploid copies of DUF1220 in hg38 (~160 of which are human-specific) and the majority of these can be divided into 6 different subtypes (referred to as clades). Copy number changes of specific DUF1220 clades have been associated in a dose-dependent manner with brain size variation (both evolutionarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…However, this gene and its role in human diseases have not been curated in OMIM. DUF1220 sequences predominantly exist in neuroblastoma breakpoint family (NBPF) genes (Astling et al, 2017). By applying specialized bioinformatics tools for analyzing the CNVs of DUF1220 from 42 patients with either the 1q21.1 deletion or the reciprocal duplications, Dumas et al (2012) proposed that the DUF1220 sequences in the NBPF genes were associated with brain size anomalies (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…However, this gene and its role in human diseases have not been curated in OMIM. DUF1220 sequences predominantly exist in neuroblastoma breakpoint family (NBPF) genes (Astling et al, 2017). By applying specialized bioinformatics tools for analyzing the CNVs of DUF1220 from 42 patients with either the 1q21.1 deletion or the reciprocal duplications, Dumas et al (2012) proposed that the DUF1220 sequences in the NBPF genes were associated with brain size anomalies (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant with the increase in the number of NBPF genes in the human lineage, a striking increase in the copy number of this domain was observed [ 84 ]. Moreover, a high number of copies of this domain has been found to be correlated with brain size and the severity of autism, whereas a low number of copies has been found to be correlated with the severity of schizophrenia [ 81 , 85 ]. Functional studies showed that overexpression of NBPF15 , which contains multiple copies of this domain, can increase the number of neural stem cells that can be generated from human embryonic stem cells [ 86 ].…”
Section: Other Human-specific Genes Expressed During Fetal Human Brain Developmentmentioning
confidence: 99%
“…The gene family neuroblastoma breakpoint family ( NBPF ) is characterized by domain of unknown function (DUF1220) protein domains that underwent the largest, >300, copy number expansion in humans ( Vandepoele et al 2005 ; Dumas and Sikela 2009 ; Sudmant et al 2010 , 2013 ; O’Bleness et al 2012a , 2012b ; Keeney et al 2014 ; Zimmer and Montgomery 2015 ; Astling et al 2017 ). This human-specific tandem repeat expansion was first described in 2006 ( Popesco et al 2006 ).…”
Section: Human-specific Segmental Duplications Deletions and Other mentioning
confidence: 99%